Identifying cancer tissue-of-origin by a novel machine learning method based on expression quantitative trait loci - Miao, Yongchang; Zhang, Xueliang; Chen, Sijie; Zhou, Wenjing; Xu, Dalai; Shi, Xiaoli; Li, Jian; Tu, Jinhui; Yuan, Xuelian; Lv, Kebo; Tian, Geng (Frontiers in Oncology, 2022)
Cancer of unknown primary (CUP) refers to cancer with primary lesion unidentifiable by regular pathological and clinical diagnostic methods. This kind of cancer is extremely difficult to treat and patients with CUP usually have very short survival time. Recent studies have suggested that cancer treatment targeting primary lesion will significantly improve the survival of CUP patients. Thus, it is critical to develop accurate yet fast methods to infer the tissue-of-origin (TOO) of CUP. In the past years, there are a few computational methods to infer TOO based on single omics data like gene expression, methylation, somatic mutation, and so on. However, the metastasis of tumor involves the interaction of multiple levels of biological molecules. In this study, we developed a novel computational method to predict TOO of CUP patients by explicitly integrating expression quantitative trait loci (eQTL) into an XGBoost classification model. We trained our model with the cancer genome atlas (TCGA) data involving over 7000 samples across 20 types of solid tumors. In the 10-fold cross-validation, the prediction accuracy of the model with eQTL is over 0.96, better than that without eQTL. In addition, we also tested our model in an independent data downloaded from gene expression omnibus (GEO) consisting of 87 samples across 4 cancer types. The model also achieves an f1-score of 0.7~1 depending on different cancer types. In summary, eQTL is an important information in inferring cancer TOO and the model might be applied in clinical routine test for CUP patients in the future.